Rich forests, poor countries: adapting forest conservation to economic realities - Sayer, Jeffrey A.; Swartzendruber, J.F.; Nasi, Robert; Byers, B.A. (Central African Regional Program for the Environment (CARPE) and Biodiversity Support Program, 2001)
In the Congo Basin, very large areas of species-rich forests exist in countries that are among the world's poorest. Decision makers and ordinary people in these countries are far more concerned about meeting short-term local and national needs than about long-term value of global biodiversity. Given present economic realities, it is hard to see how such investments can be sustained unless much greater emphasis is given to reconciling conservation objectives with economic needs. Forest conservation in the Congo Basin will require more diversified approahes in order to manage a wider range of land-use systems more effectively, at lower cost, and with significant more local and national participation. The current enthusiasm for the big, remote, pristine parks model of forest conservation is risky.